PENGUJIAN TOTAL PLATE COUNT DALAM PEMBUATAN BAKSO IKAN KEMBUNG BERBAHAN DASAR TEPUNG SAGU DENGAN PENAMBAHAN DAUN SALAM - Dahlan, Sakinah Ahyani (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2023)
Fish is an economical protein source with significant nutritional value, providing easily digestible protein and versatile cooking options. A popular modified version of processed mackerel is the fish ball or 'bakso,' commonly found in Indonesian cuisine. Bakso, a prevalent type of meatball, is crafted using mackerel and substituting flour, often opting for sago flour. Sago flour, as a food ingredient, can be consumed directly or incorporated into various food industry applications. Ongoing research is dedicated to exploring natural preservatives as an alternative to chemical preservatives due to their adverse effects. Research findings suggest that bay leaf extract can prolong the shelf life of mackerel fish balls stored at room temperature for up to 36 hours. Bay leaves exhibit antibacterial properties against pathogenic bacteria. Total Plate Count (TPC) testing in a laboratory stands out as a method for detecting and analyzing microbial content in food.